The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1016/j.jcrs.2004.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of implantation of phakic posterior chamber intraocular lenses

Abstract: Risk factors for lens opacification after implantation of the model V4 ICL included intraoperative trauma to the crystalline lens and older age. Decreased ECD in eyes with opacification suggests ongoing inflammation as a cause. Patients younger than 45 years may have a significantly lower incidence of opacification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 26 publications
3
96
0
3
Order By: Relevance
“…Increased flare has also been found after the implantation of a posterior chamber pIOL. 13,14 We did not report any case of retinal detachment or endophthalmitis after implantation of either Artisan or ICL. One report showed that the risk of retinal detachment in pIOL cases was lower than in clear lens extraction cases.…”
Section: Discussionmentioning
confidence: 83%
“…Increased flare has also been found after the implantation of a posterior chamber pIOL. 13,14 We did not report any case of retinal detachment or endophthalmitis after implantation of either Artisan or ICL. One report showed that the risk of retinal detachment in pIOL cases was lower than in clear lens extraction cases.…”
Section: Discussionmentioning
confidence: 83%
“…With regard to patient age, Gonvers et al 12 reported that ICL-induced cataracts develop more frequently in older patients than in younger patients; the incidences in those of 40 years of age or less and of 41 or over were 14 and 37%, respectively. Lackner et al 13 and Sarikkola et al 14 proposed ages of 50 years or older and 45 years or older, respectively, as risk factors for cataract development after ICL implantation. Fujisawa et al 15 stated that a decrease in accommodation with ageing may affect the continuous flow of the aqueous humour, resulting in a higher incidence of cataract development after ICL implantation.…”
Section: Discussionmentioning
confidence: 99%
“…In our preliminary data, pupil dilation tends to slightly increase the amount of vaulting, but this increase between pre-and postmydriasis remains constant (unpublished data). In addition, it has been reported that the vaulting showed a tendency to decrease slightly over time, 16,41 suggesting that ICL collamer material may not have a permanent memory. Further studies with longer follow-ups are required for longitudinal assessment of the behaviour of the ICL.…”
Section: Discussionmentioning
confidence: 99%